Does statin increase the risk of intracerebral hemorrhage in stroke survivors? A meta-analysis and trial sequential analysis. (July 2019) - Teoh, Ru Jian Jonathan; Huang, Chi-Jung; Chan, Chi Peng; Chien, Li-Yin; Chung, Chih-Ping; Sung, Shih-Hsien; Chen, Chen-Huan; Chiang, Chern-En; Cheng, Hao-Min
Background: It remains debatable whether statin increases the risk of intracerebral hemorrhage (ICH) in poststroke patients. Methods: We systematically searched PubMed, EMBASE, and CENTRAL for randomized controlled trials. Trial sequential analysis (TSA) was conducted to assess the reliability and conclusiveness of the available evidence in the meta-analysis. To evaluate the overall effectiveness, the net composite endpoints were derived by totaling ischemic stroke, hemorrhagic stroke, transient ischemic attack (TIA), myocardial infarction, and cardiovascular mortality. Results: A total of 17 trials with 11, 576 subjects with previous ischemic stroke, TIA, or ICH were included, in which statin therapy increased the risk of hemorrhagic stroke (risk ratio [RR], 1.42; 95% confidence interval [CI], 1.07–1.87), but reduced the risk of ischemic stroke (RR, 0.85; 95% CI, 0.75–0.95). For the net composite endpoints, statin therapy was associated with a 17% risk reduction (95% CI, 12–21%; number needed to treat = 6). With a control event rate 2% and RR increase 40%, the TSA suggested a conclusive signal of an increased risk of hemorrhagic stroke in stroke survivors taking statin. However, with the sensitivity analysis by changing assumptions, the conclusions about hemorrhagic stroke risk were less robust. Conclusions: Statin therapy in poststroke patients increased the risk of hemorrhagic stroke but effectively reduced ischemic stroke risk. Weighing the benefits and potential harms, statin has an overall beneficial effect in patients with previous stroke or TIA. However, more studies are required to investigate the conclusiveness of the increased hemorrhagic stroke risk revealed in our study.